Babesia bovis AMA-1, MSA-2c and RAP-1 contain conserved B and T-cell epitopes, which generate neutralizing antibodies and a long-lasting Th1 immune response in vaccinated cattle - Hidalgo-Ruiz, Mario (2022)
Vaccines against bovine babesiosis must, ideally, induce a humoral immune response characterized by neutralizing antibodies against conserved epitopes and a cellular Th1 immune response. In Babesia bovis, proteins such as AMA-1, MSA-2c, and RAP-1 have been characterized and antibodies against these proteins have shown a neutralizing effect, demonstrating the implication of B and T-cell epitopes in the immune response. There is evidence of the existence of B and T-cell epitopes in these proteins, however, it remains to be defined, the presence of conserved peptides in strains from around the world containing B and T-cell epitopes, and their role in the generation of a long-lasting immunity. The aim in this paper was to identify peptides of Babesia bovis AMA-1, MSA-2c, and RAP-1 that elicit a neutralizing and long-lasting Th1 immune response. Peptides containing B-cell epitopes of AMA-1, MSA-2c and RAP-1, were identified. The immune response generated by each peptide was characterized in cattle. All peptides tested induced antibodies that recognized intraerythrocytic parasites, however, only 5 peptides generated neutralizing antibodies in vitro: P2AMA-1 (6.28%), P3MSA-2c (10.27%), P4MSA-2c (10.42%), P1RAP-1 (32.45%), and P4RAP-1 (36.98%). When these neutralizing antibodies were evaluated as a pool, the inhibition percentage of invasion increased to 52.37%. When the T cellular response was evaluated, two peptides: P3MSA2c and P2AMA1 induced a higher percentage (>70%) of activated CD4 +/CD45RO+ T cells than unstimulated cells. Additionally, both peptides induced the production of gamma interferon (IFN-) in PBMCs from vaccinated cattle after one year proving the implication of a long-lasting Th1 immune response. In conclusion, we identified conserved peptides containing B and T-cell epitopes in antigens of B. bovis that elicit a Th1 immune response and showed evidence that peptides from the same protein elicit different immune responses, which has implication for vaccine development in bovine babesiosis.